Penerapan Business Model Canvas untuk Pengembangan Bisnis TemplateKuy dalam Penyediaan Template Notion dan Spreadsheet - Ramdhana, Muhammad Fathi; Maryadi, Muhammad Rahmat; Aji, Wahyu Mustika; Matouq, Hassan Nasrallah; Kuntari, Wien (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
In the rapidly evolving digital era, effective business models are crucial for sustaining competitiveness. This research explores the application of the Business Model Canvas (BMC) to TemplateKuy, a digital platform providing Notion and Spreadsheet templates. The study aims to identify how BMC's nine components—customer segments, value propositions, channels, customer relationships, revenue streams, key resources, key activities, key partnerships, and cost structures—can be optimized for business growth and sustainability. A qualitative descriptive method was employed, involving interviews, observations, and SWOT analysis to evaluate TemplateKuy’s strategic positioning. The findings reveal that BMC helps TemplateKuy create tailored strategies that align with market demands, improve operational efficiency, and increase value for its users. However, challenges such as resource limitations and market competition persist. These results offer valuable insights for similar businesses aiming to leverage BMC for strategic planning. The study emphasizes the importance of continuous innovation and customer feedback to maintain relevance in the dynamic digital industry.